2022
DOI: 10.1039/d2ta03325a
|View full text |Cite
|
Sign up to set email alerts
|

A single atom Ir doped heterophase of a NiMoP-NiMoPxOy ultrathin layer assembled on CNTs-graphene for high-performance water splitting

Abstract: For bifunctional water splitting, the rational construction of efficient and robust catalysts with cost-effective and high-performance electrocatalysts study in industrial green H2 production. In this study, single atom Ir into...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…18 NiMoP phases, observing a 90 mV overpotential to achieve a current density of 10 mA cm −2 for HER. 20 Shao et al loaded Ir nanoclusters onto covalent organic polymers (Ir-COP), which showed high activity for water splitting in both alkaline and acidic electrolytes. 21 These studies demonstrate that loading the small size Ir atoms and nanoclusters on the support material by forming the efficient electron interactions will be a good strategy for realizing the optimum catalytic activity of Ir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 NiMoP phases, observing a 90 mV overpotential to achieve a current density of 10 mA cm −2 for HER. 20 Shao et al loaded Ir nanoclusters onto covalent organic polymers (Ir-COP), which showed high activity for water splitting in both alkaline and acidic electrolytes. 21 These studies demonstrate that loading the small size Ir atoms and nanoclusters on the support material by forming the efficient electron interactions will be a good strategy for realizing the optimum catalytic activity of Ir.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al utilized the electrochemical deposition method to anchor Ir atoms on Ni (3‑ x ) Fe x S 2 nanosheets, which exhibit excellent OER performance in alkaline electrolyte due to the optimized interactions between Ir atoms and the sulfide substrate . Kim et al introduced Ir atoms into amorphous NiMoP x O y and crystalline NiMoP phases, observing a 90 mV overpotential to achieve a current density of 10 mA cm –2 for HER . Shao et al loaded Ir nanoclusters onto covalent organic polymers (Ir-COP), which showed high activity for water splitting in both alkaline and acidic electrolytes .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, when the TMP phase is properly integrated with another conductive phase like carbon species, the electron transfer rate can be further improved, and TMPs can be stabilized by the conductive backbones without agglomeration. 16 Second, the rich lattice defects and unsaturated atoms at the interfaces not only can serve as new active sites, but also produce abundant dangling bonds as acceptors for uniformly loading and tightly stabilizing the metal SAs. 17 The construction of a multi-heterogeneous structure can further increase the lattice defects and unsaturated atoms.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate this process, researchers typically use the Gibbs free energy of adsorbed hydrogen (ΔG H* ) to characterize: the closer the value of ΔG H* is to 0, the better the catalytic effect. [29][30][31] Based on this principle, a volcanic curve can be obtained. And as can be seen in Figure 3, the ΔG H* of noble metals is closest to 0, so noble metals have naturally high activity compared with non-precious metals.…”
Section: Introductionmentioning
confidence: 99%